Risk Factors for Initial Febrile Seizures in Pediatric Patients at Iranian Tertiary Hospitals (2019-2021): Retrospective Cross-Sectional Study - Mohammadi, Mahya Sadat; Soti Khiabani, Mahsa; Nemati, Roghaye; Yarali, Baram; Dehghan, Amir Hossein; Rezaei, Zahra (Iranian Journal of Child Neurology, 2026)
Objectives: Febrile seizures (FS) are among the most common neurological emergencies in children aged 6 months to 6 years, yet their risk factors remain poorly defined in Iran. This study aimed to identify and analyze the demographic, clinical, and laboratory factors associated with the first episode of febrile convulsion (FC) in children admitted to a major pediatric hospital in Tehran, Iran. Materials & Methods: This retrospective cross-sectional study was conducted at a large pediatric hospital in Tehran, Iran, from 2019 to 2021. A total of 305 children who met the predefined inclusion criteria were included. Data were extracted from medical records and supplemented by interviews with caregivers. Collected variables included seizure type, perinatal history, family history of febrile seizures, serum biomarkers (e.g., hemoglobin, sodium), cause of fever, and other relevant clinical factors. Results: Of the seizures, 85.2% were simple and predominantly occurred within the first 24 hours of fever onset. Complex seizures showed a significant association with preterm delivery (P=0.02) and a positive family history of febrile seizures (P=0.01). Anemia was significantly more common in girls (P=0.027), and hemoglobin levels tended to be lower in children with complex seizures, although this difference was not statistically significant (P=0.06). Serum sodium levels remained within the normal range in all groups. Routine electroencephalography (EEG) showed abnormal findings in only 0.66% of cases, questioning its routine diagnostic value in first febrile seizures. Antihistamine use was uncommon and showed no association with seizure characteristics. The most frequent underlying causes of fever were upper respiratory tract infections, viral gastroenteritis, and post-vaccination fever. Conclusion: This study provides novel regional insights into the pathophysiological and epidemiological features of first febrile seizures in Iranian children. The findings highlight specific risk factors for complex seizures (preterm birth and family history) and suggest that targeted screening and preventive strategies could benefit high-risk pediatric populations. The very low yield of routine EEG supports a more selective approach to its use in this setting